2006
DOI: 10.1021/ac060526n
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Continuous Full Filling Capillary Electrochromatography/Electrospray Ionization-Mass Spectrometry for Separation of Neutral Compounds

Abstract: Highly efficient reversed-phase capillary electrochromatography (CEC) separations (plate numbers up to 700 000/m), with electrospray ionization mass spectrometry detection were achieved utilizing novel dextran-coated polymer nanoparticles as a pseudostationary phase. A continuous full filling (CFF) technique in which nanoparticles are continuously introduced into the capillary was employed for separation of neutral analytes (dialkyl phthalates), utilizing an orthogonal electrospray interface to prevent nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 37 publications
2
68
0
Order By: Relevance
“…For this reason, 25% acetonitrile in both BGE and sheath liquid was found being optimal, presenting a local maximum in the surface plots ( Figure 4). Although the composition of the sheath liquid previously has remained uninvestigated the effects of the organic modifier concentration in the BGE has been investigated in two previous studies [24,25]. These studies showed, as also shown here, that the efficiency increased while the resolution decreased with increasing acetonitrile concentration in the BGE.…”
Section: Sheath Liquid and Organic Modifiersupporting
confidence: 60%
See 2 more Smart Citations
“…For this reason, 25% acetonitrile in both BGE and sheath liquid was found being optimal, presenting a local maximum in the surface plots ( Figure 4). Although the composition of the sheath liquid previously has remained uninvestigated the effects of the organic modifier concentration in the BGE has been investigated in two previous studies [24,25]. These studies showed, as also shown here, that the efficiency increased while the resolution decreased with increasing acetonitrile concentration in the BGE.…”
Section: Sheath Liquid and Organic Modifiersupporting
confidence: 60%
“…Thus, from these studies it can be concluded that the optimal nanoparticle concentration is 3.8 mg/mL, and that the presence of nanoparticles in the electrospray does not influence the ionization efficiency. In a previous study on CFF-CEC/ESI-MS, Nilsson et al indicated that for dextran coated polymer nanoparticles, the optimal particle concentration was 5 mg/mL [24]. However, the data was not replicated in that study and no thorough analysis of the data was performed.…”
Section: Nanoparticle Concentrationmentioning
confidence: 91%
See 1 more Smart Citation
“…7,8 NPs were also used in electrophoresis techniques, either as modifiers to the wall of capillary or microchip, [9][10][11][12] or as pseudostationary phases (PSPs) in which they were added into the running buffers. [13][14][15] NPs used as PSPs can be replaced from run to run, and the stationary carry-over effects are thus avoided, favoring sample analysis in complex matrices. 16 Since the first report by Wallingford and Ewing, 17 various NPs to date have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…13 The same research group employed NPs as PSPs in separation of neutral compounds, and they reported plate numbers as high as 700000/m. 14 Chang's group employed gold nanoparticles (GNPs) as additives in CE separation of DNA fragments. [23][24][25][26] Due to the interaction of DNA fragments with the GNPs, the apparent mobilities of DNA fragments changed, and the plate numbers doubled.…”
Section: Introductionmentioning
confidence: 99%